Role of Trust on Organizational Citizenship Behavior (OCB): Perspective from The Employee on the Retail Sector in Bandung, Indonesia - Ester Manik (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2020)
Individual behavior that can increase organizational effectiveness is an essential aspect for organizations to achieve optimal performance. For this reason, there is a need for research that can contribute to improving individual behavior in producing its effectiveness. However, previous research has shown a theoretical gap in measuring individual trust and organizational citizenship behavior. In theory, to fill the gap, this study measures the influence of individual beliefs and organizational citizenship behavior. Researchers surveyed employees who work in the retail sector as many as 257 employees. The researchers used a structural equation modeling approach – PLS with predictive purposes to test the research model. The study results indicate that there is a positive influence on individual beliefs based on intention and individual beliefs on actions on organizational citizenship behavior. The study's implications indicate the need to increase the motivational aspect to increase individual confidence so that it will lead to behavioral actions that can increase organizational effectiveness.